2016
DOI: 10.18203/2349-2902.isj20151534
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric appendicitis scoring: a useful guide to diagnose acute appendicitis in children

Abstract: Background: Pain in abdomen is common reason for which a child is brought to a surgeon and acute appendicitis is one of the common differential diagnoses in these children. In spite of availability of modern radiological and pathological investigations, even today the diagnosis of acute appendicitis depends mainly on clinical grounds and simple blood count. Pediatrics appendicitis scoring (PAS) which is based on clinical symptoms and sign along with WBC count is a good guide in diagnosis of acute appendicitis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…2 Majority of the children included in the present study were males (61%) and 56.7% of children did not have appendicitis which is similar to findings in other studies .6-8 Anorexia, emesis, migration pain, cough tenderness and leukocytosis were the features most consistently seen in appendicitis which is comparable to other studies. 1,6,8 Children with PAS of 3, had same PAS even after 6 hours. Only 1 out of the 10 children with PAS ≤3 underwent surgery and biopsy done showed appendicitis.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…2 Majority of the children included in the present study were males (61%) and 56.7% of children did not have appendicitis which is similar to findings in other studies .6-8 Anorexia, emesis, migration pain, cough tenderness and leukocytosis were the features most consistently seen in appendicitis which is comparable to other studies. 1,6,8 Children with PAS of 3, had same PAS even after 6 hours. Only 1 out of the 10 children with PAS ≤3 underwent surgery and biopsy done showed appendicitis.…”
Section: Discussionmentioning
confidence: 82%
“…Rate of negative appendicectomy in the present study was 0%, which is similar to another study. 8 Diagnostic imaging has been used with increasing frequency but has limitations, including exposure to ionizing radiation (e.g., computed tomography), limited availability of skilled technicians at all hours (e.g. ultrasound) and cost.…”
Section: Discussionmentioning
confidence: 99%
“… 20 Another study also documented that PAS≥7 was strongly indicative of appendicitis and reported rate of negative appendectomy as 0%. 21 A local study showed that Alvarado score of 6 or more has a diagnostic accuracy of 82.9% in predicting acute appendicitis in children. 22 Still in this RCT we have used criteria of PAS≥7 for enrolling patients.…”
Section: Discussionmentioning
confidence: 99%